RESPONS PETANI TERHADAP PENGENDALIAN HAMA TIKUS DENGAN BURUNG HANTU DI KECAMATAN SEDAYU KABUPATEN BANTUL - Mukti Ahmad Nucrahya; Roso Witjaksono; Subejo Subejo (Agro Ekonomi, 2015)
The goal of this research is tofigure out the level offarmer response and the influencingfactors on rats control by Tyto alba. The used basic method was analytical descriptive- by survey technique. Sedayu Sub-District in Bantul District was chosen as research location because of the rats controlling programme has been newly started in Sedayu SubDistrict. Sample of farmers was selected by simple random sampling. The respondents were choosen from 60 farmers from 4 villages in Sedayu Sub-District. The research results of this research showed that farmers response to rats controlling by Tyto alba was in high category. Factors that influence the rats controlling were knowledge to Tyto alba and perception. While age, education level, farming experience, position on farmer group, knowledge to Integrated Pest Control (IPC), intensity to join extension, motivation, land size, and field extension workers' role did not affect the farmers response.